Proposal of the Slovene terminology on slope movements - slope transport - Skaberne, Dragomir (Geologija, 2001)
Slovene terminology, synonymy for English terms, on gravity slope movements, and their genetic classification is proposed. Short definitions and descriptions of processes and their products are given. The treated terms represent end members within complex mechanisms of gravity slope movements: topple, fall, slide and flows (grain flow, debris flow, liquified/fluidized flow, turbidity currents - hyperconcenrated stream flow).